Hegemonia e empiria histórica - Manieri, Dagmar (2019)
The objective of this work is a study of the application of the concept of hegemony in historical research. This implies an abandonment of the traditional historical narrative and a foundation of the writing according to a mediating concept. In this last form of writing, history receives a critical reading, according to the logic of the mediating concept. In our example, hegemony implies a form of domination that does not occur exclusively in the political order. This explains, in part, the intentionality of historical agents in their multiple forms of domination.